Study on Educational Management and Development of Educational Institutions - Wirtati, Ira; Nurdiana, Nurdiana (EDUTEC : Journal of Education And Technology, 2024)
This study aims to examine the development model of Islamic educational institutions, specifically focusing on MTs Islamiyah YPI Batang Kuis, to understand the stages and strategies utilized in managing institutional growth and curriculum integration. Using a qualitative, phenomenological approach, this research collects data through observation, interviews, and documentation. Findings reveal a four-stage institutional development model: (1) Diagnosis, where the madrasah head identifies and analyzes institutional challenges; (2) Intervention, which involves implementing solutions to address these challenges; (3) Evaluation, through which the outcomes of interventions are assessed; and (4) Maintenance, aiming to sustain and refine the positive results achieved. Furthermore, MTs Islamiyah YPI Batang Kuis operates as a full-day school, utilizing a dual-curriculum model from both the Ministry of National Education and the Ministry of Religious Affairs, highlighting a structured approach to Islamic education management.